ERRORS WHEN USING TELESCOPIC SURVEY STAFF IN GEOMETRIC LEVELING: ERRORS WHEN USING TELESCOPIC SURVEY STAFF IN GEOMETRIC LEVELING - Ivanov, Ivan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Geometric leveling is the most accurate method of determining the difference between two points used in surveying. By using calibrated equipment and applying the correct measurement methodology, accuracy can be achieved to a hundredth of a millimeter for individual measurement or to 0.2mm/km for double-run leveling. The equipment consists of a precision level (usually digital) and a surveying staff, which is often considered as auxiliary equipment, but in reality the surveying staff is no less important than the level itself [1]. Given the wear and tear and depreciation of the equipment, it should be periodically checked and, if necessary, calibrated. The results of the calibration allow correction of the raw data, and can also serve as a preliminary assessment and forecast of the achieved results.